ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI LAPAS KELAS IIB BIREUEN - Iqval Brian Hanafi; Raihan Iskandar; Rizka Sylvia (IndOmera, 2025)
The study aimed to analyze job satisfaction related to compensation and the work environment and their impact on employee performance. Quantitative associative research was used, and path-wise data analysis was used. The study was conducted on 58 employees of Class IIB Bireuen Prison. The results showed that (1) compensation had a direct and indirect effect on job satisfaction, through the work environment variable, amounting to 34.4%. (2) compensation had a direct and indirect effect on job satisfaction, through the compensation variable, amounting to 46.17%. (3) Compensation and the work environment simultaneously contributed to job satisfaction, amounting to 81.2%. (4) Compensation had a direct and indirect impact on employee performance, amounting to 42.75%. The work environment had an impact of 49.83%. (5) The total effect of compensation and the work environment on employee performance, through the job satisfaction variable, was 18%. (6) The contribution of compensation and the work environment to employee performance was 71.2%